Approaching hemophagocytic lymphohistiocytosis - Chinnici, Aurora; Beneforti, Linda; Pegoraro, Francesco; Trambusti, Irene; Tondo, Annalisa; Favre, Claudio; Coniglio, Maria Luisa; Sieni, Elena (Frontiers in Immunology, 2023)
Hemophagocytic Lymphohistiocytosis (HLH) is a rare clinical condition characterized by sustained but ineffective immune system activation, leading to severe and systemic hyperinflammation. It may occur as a genetic or sporadic condition, often triggered by an infection. The multifaceted pathogenesis results in a wide range of non-specific signs and symptoms, hampering early recognition. Despite a great improvement in terms of survival in the last decades, a considerable proportion of patients with HLH still die from progressive disease. Thus, prompt diagnosis and treatment are crucial for survival. Faced with the complexity and the heterogeneity of syndrome, expert consultation is recommended to correctly interpret clinical, functional and genetic findings and address therapeutic decisions. Cytofluorimetric and genetic analysis should be performed in reference laboratories. Genetic analysis is mandatory to confirm FHL and Next Generation Sequencing is increasingly adopted to extend the spectrum of genetic predisposition to HLH, though its results should be critically discussed with specialists. In this review, we critically revise the reported laboratory tools for the diagnosis of HLH, in order to outline a comprehensive and widely available workup that allows to reduce the time between the clinical suspicion of HLH and its final diagnosis.